Effect of the Unsteadiness on the Diffuser Flow in a Transonic Centrifugal Compressor Stage - N. Bulot; I. Trébinjac (International Journal of Rotating Machinery)
The study is focused on the analysis of the flow structure within the vaned diffuser of a transonic high-pressure centrifugal compressor stage. The analyzed time-dependent flow field comes from unsteady computations of the stage using a 3D Navier-Stokes code with a phase-lagged technique, at an operating point close to the design point. A good comparison with available experimental data allowed the use of CFD for investigating the details of the flow in order to assess the effect of the unsteadiness in the diffuser flow development. Applying various data processing techniques, it is shown that the unsteadiness is due to the jet and wake flow structure emerging from the radial impeller and to the pressure waves brought about by the interaction between the vane bow shock wave and the impeller blade. The interaction between the pressure waves and the vane pressure side boundary layer leads to a pulsating behavior of separated bubbles within the diffuser. The pressure waves are similar in shape and strength whatever the blade height. The observed change in the flow field from hub to tip is due to migration of the low momentum fluid contained in the wake toward the pressure side/hub corner.